Effectiveness of the Working Environment on Labor Productivity - Enchevski, Encho (Research Papers, 2018)
In a rapidly changing business environment, it is vital for organizations to use every source of competitive advantage. The purpose of the article is to analyze scientific literature to determine how labor productivity can be improved through changes in the work environment. This is decomposed into the following tasks - clarifying the essence of labor productivity and the elements of the work environment; identifying the possible contribution of each element. A model is selected that contains different variables and their impact is analyzed. The work environment has many elements and their understanding is important for its proper management.
Keywords: Corporate real estate; Work environment; Labor productivity